Record 47 mV/dec top-down vertical nanowire InGaAs/GaAsSb tunnel FETs - Alian, Alireza; Kazzi, Salim El; Verhulst, Anne; Milenin, Alexey; Pinna, Nicolo; Ivanov, Tsvetan; Lin, Dennis; Mocuta, Dan; Collaert, Nadine (2018 IEEE Symposium on VLSI Technology, 2018)
Pocketed vertical nanowire InGaAs/GaAsSb tunnel FETs (TFET) with sub-threshold swing (SS) reaching 47 mV/dec are demonstrated. The achieved sub-threshold performance is the steepest reported so far for a top-down TFET in the III-V material system. Smooth vertical wires with diameters as narrow as 30 nm are achieved using a CH 4 based dry etch process. Drive current at 0.35 V supply voltage approaches 0.7 μA/μm for a fixed I off of 1 nA/μm.